TRADISI PANTANGAN MENIKAH DI ANTARA KHUTBAH IDULFITRI DAN IDULADHA: ANALISIS FENOMENOLOGI DALAM MASYARAKAT TANOYAN UTARA - Paputungan, Senta Febriya Paputungan; Haq, Yusdi (LPPM STAI Muhammadiyah Probolinggo, 2025)
The purpose of this study is to investigate the history of the custom of forbidding marriages between the sermons of Eid al-Fitr and Eid al-Adha. Additionally, it will examine how the Tanoyan Utara community and Islamic law see this custom. Through in-depth interviews, observation, and a survey of the literature, this study employs a qualitative methodology with a phenomenological analytic method. The results show that the restriction is not based on Islamic law texts but comes from deep-rooted beliefs shaped by social influences, traditional recognition, and stories passed down through generations. While the younger generation prefers to take a more logical stance based on Islamic legal evidence, the older generation sees this tradition as a cultural heritage that needs to be honored. From an Islamic legal standpoint, according to Islamic law, the custom of not getting married between the two Eids has no legitimate legal foundation. On the contrary, Islam forbids the belief in unlucky periods (ṭiyārah) and promotes the idea that marriage should not be postponed without good cause